Meningkatkan Akhlakul Karimah Anak Usia Dini Melalui Metode Pembiasaan - Isman Efendi Limbong; Isropil Siregar (Yayasan Rahmat Islamiyah, 2022)
Morality can fix all the ugliness of appearance and deceptive external forms. So that he becomes an interpreter for what is hidden within a person. Actually, when the word